PERK 1/2 inhibit Caspase‐8 induced apoptosis in cancer cells by phosphorylating it in a cell cycle specific manner. Issue 2 (20th November 2013) - Mandal, Ranadip; Raab, Monika; Matthess, Yves; Becker, Sven; Knecht, Rainald; Strebhardt, Klaus
Abstract : ERK 1/2 are found to be hyperactive in many cancers. Active ERK 1/2 (pERK 1/2) are known to protect cancer cells from undergoing death receptor‐mediated apoptosis, although the mechanism(s) behind this is poorly understood. Through in vitro kinase assays and mass‐spectrometry we demonstrate that pERK 1/2 can phosphorylate pro‐Caspase‐8 at S387. Also, in EGFR‐overexpressing Type I and II ovarian and breast cancer cell lines respectively, ERK 1/2 remain active only during the interphase. During this period, pERK 1/2 could inhibit Trail‐induced apoptosis, most effectively during the G1/S phase. By knocking‐down the endogenous pro‐Caspase‐8 using RNAi and replacing it with its non‐phosphorylatable counterpart (S387A), a significant increase in Caspase‐8 activity upon Trail stimulation was observed, even in the presence of pERK 1/2. Taken together, we propose that a combination of Trail and an inhibitor of ERK 1/2 activities could potentially enhance of Trail's effectiveness as an anti‐cancer agent in ERK 1/2 hyperactive cancer cells. Highlights: pERK 1/2 inhibit Caspase‐8 activation by phosphorylating it at its S387 residue. pERK 1/2 protect both Type I and II cancer cells from Caspase‐8 derived apoptosis. This phosphorylation occurs during the interphase, most prominently during the G1/S phase, of SKOV3 and MDA‐MB‐468 cells. Replacing cellular Caspase‐8 with non‐phosphorylatable mutant enhances apoptosis. Cdk1 and pERK 1/2 and possibly Cdk2 can protect cancer cells from apoptosis throughout the cell cycle.